THE HIGH ACHIEVERS’ STRATEGIES IN ANSWERING READING COMPREHENSION IN TOEFL - Wicaksono, Agung; Jatmiko, Jatmiko (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This study is to describe the high achievers’ strategies in answering reading comprehension in TOEFL. As we know there are many strategies used in answering this section, so this study finds out the essential strategies used by the high achievers in TOEFL. It is descriptive study that employed qualitative approach. The subject of this study was 5 the high achievers of Nusantara PGRI University. The sample was selected using purposive sampling technique; they were selected by having score more than 500 and achieved high score in reading comprehension section. The data collected by interviewing the high achievers, so interview used as a data collection technique. The findings show that various used in answering reading comprehension. There eight essential strategies used by the high achievers to answer reading comprehension include vocabulary in TOEFL.